Gender and agricultural mechanization: A mixed-methods exploration of the impacts of multi-crop reaper-harvester service provision in Bangladesh - Theis, Sophie; Krupnik, Timothy J.; Sultana, Nasrin; Rahman, Syed-Ur; Seymour, Greg; Abedin, Naveen (International Food Policy Research Institute, 2019)
Farmer hiring of agricultural machinery services is common in South Asia. Informal fee-for-service arrangements have positioned farmers so they can access use of machinery to conduct critical, timesensitive agricultural tasks like land preparation, seeding, irrigation, harvesting and post- harvesting operations. However, both the provision and rental of machinery services are currently dominated by men, and by most measures, it appears that women have comparatively limited roles in this market and may receive fewer benefits. Despite the prevailing perception in rural Bangladesh that women do not participate in agricultural entrepreneurship, women do not necessarily lack a desire to be involved. Using a mixed methods approach involving literature review, secondary data collection, focus groups and key informant interviews, and a telephone survey, we studied the gendered differences in women’s and men’s involvement in emerging markets for rice and wheat reaper-harvester machinery services in Bangladesh. We find that women benefit from managing and sometimes owning machinery services, as well as from the direct and indirect consequences of hiring such services to harvest their crops. However, a number of technical, economic, and cultural barriers appear to constrain female participation in both reaper service business ownership and in hiring services as a client. In addition, women provided suggestions for how to overcome barriers constraining their entry into rural machinery services as an entrepreneur. Men also reflected on the conditions they would consider supporting women to become business owners. Our findings have implications for addressing social norms in support of women’s rural entrepreneurship and technology adoption in South Asia’s smallholder dominated rural economies.